Family Health Conversations: How Do They Support Health? - Carina Persson; Eva Benzein (Nursing Research and Practice)
Research shows that living with illness can be a distressing experience for the family and may result in suffering and reduced health. To meet families’ needs, family systems intervention models are developed and employed in clinical contexts. For successful refinement and implementation it is important to understand how these models work. The aim of this study was therefore to describe the dialogue process and possible working mechanisms of one systems nursing intervention model, the Family Health Conversation model. A descriptive evaluation design was applied and 15 transcribed conversations with five families were analyzed within a hermeneutic tradition. Two types of interrelated dialogue events were identified: narrating and exploring. There was a flow between these events, a movement that was generated by the interaction between the participants. Our theoretically grounded interpretation showed that narrating, listening, and reconsidering in interaction may be understood as supporting family health by offering the families the opportunity to constitute self-identity and identity within the family, increasing the families’ understanding of multiple ways of being and acting, to see new possibilities and to develop meaning and hope. Results from this study may hopefully contribute to the successful implementation of family systems interventions in education and clinical praxis.